2021
DOI: 10.24843/eja.2021.v31.i05.p02
|View full text |Cite
|
Sign up to set email alerts
|

Determinan yang Berpengaruh pada Minat Investasi di Pasar Modal

Abstract: Investing in the capital market is an alternative for people who want to invest their excess funds as well as being able to drive the economy in a country. This study aims to obtain empirical evidence regarding the determinants that influence investment interest in the capital market. Determination of the sample in this study using purposive sampling method with a sample of 105 students who have taken the capital market theory course and already have an account of effects. The data analysis technique used is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
0
3
0
5
Order By: Relevance
“…Pernyataan ini didukung oleh hasil penelitian Saraswati & Wirakusuma (2018), Darmawan dkk. (2019), Nisa & Zulaika (2017) dan Dewi & Gayatri (2021) yang menyatakan bahwa terdapat pengaruh antara motivasi dengan minat berinvestasi.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Pernyataan ini didukung oleh hasil penelitian Saraswati & Wirakusuma (2018), Darmawan dkk. (2019), Nisa & Zulaika (2017) dan Dewi & Gayatri (2021) yang menyatakan bahwa terdapat pengaruh antara motivasi dengan minat berinvestasi.…”
Section: Pendahuluanunclassified
“…Literasi keuangan yang dimiliki oleh seseorang membantu seseorang dalam pengambilan keputusan yang efektif berkaitan dengan keuangan (Susdiani, 2017). Penelitian Parulian & Aminnudin (2020), Darmawan dkk., (2019) dan Pangestika & Rusliati (2019) Riset ini merupakan replikasi dari penelitian Dewi & Gayatri (2021) dengan variabel literasi keuangan dan lingkungan keluarga sebagai tambahan variabel untuk membedakan dengan penelitian sebelumnya. Penelitian ini menjadi menarik berdasarkan data dan kasus terkait minat mahasiswa berinvestasi di pasar modal serta adanya hasil penelitian terdahulu yang inkonsisten terkait minat mahasiswa di pasar modal yang menjadi alasan peneliti untuk melakukan penelitian ini.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…This is entirely appropriate with the Decision Making Theory, which contends that choosing one course of action from a list of alternatives in order to solve a problem or take advantage of an opportunity is the process of making decisions. Numerous unpredictable future occurrences are decided upon (Dewi & Gayatri, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Investment interest has been thoroughly investigated in earlier studies. Research by Dewi & Gayatri (2021) probed the factors that affect investors' motivation in the capital market. Their research's findings showed that the bandwagon effect, investor motivation, and understanding of investing concepts all had a favorable impact on investors' interest in the capital market.…”
Section: Introductionmentioning
confidence: 99%